بيع الدين وتطبيقاته المعاصرة في المؤسسات المالية الإسلامية الماليزية - عثمان، عافه محمد سعيد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This research addresses the topic of debt sale and its applications in contemporary Malaysian Islamic financial institutions, whose ways, causes and methods are resorted to by those of low-income in particular and the rest of society in general, as it responds to their living necessities. Thus this study highlights the reasons for the emergence of debt, its concept, its legitimacy, and the provisions of its sale in different forms.It also touches upon the concept of the creditor and the debtor, the subsequent benefit or harm as a result of debt, and the importance of documenting it without excluding its relationship with credit sale in Islamic jurisprudence. The study also examines contemporary debt sale applications in the Malaysian Islamic financial institutions in the light of the purposes of Islamic law, the Malaysian Islamic securities market, the importance of Securitization, and an evaluation of the success of the Malaysian experience in debt sale. In addition, the study recommends a reconsideration of these sales' applications by those in authority, who are involved in Islamic finance, with regard to the observance of Islamic and legal regulations. The researcher utilized the inductive and descriptive approaches to collect the data by tracing the views of former and contemporary jurists; the critical-analytical method was also needed for the discussion and analysis of those views and evidence, grounded on the approach of comparative jurisprudence.Moreover, the researcher conducted some interviews with some Malaysian academic figures as well as a number of people working in the Shari'ah Supervisory Board and Islamic legislation of Islamic banks.The study uncovers the prohibition of trading in debt unless it is a case of determinate properties and goods with a commitment to the conditions and regulations of Islamic Law; it suggests the permission of debt sale to the debtor as taking possession of the price is not required; the same applies to a non-debtor committed to the conditions and regulations set by the jurists.